Inflammatory Response of Tumor Necrosis Factor-alpha (TNF-α) in Incised Wounds of White Rats (Rattus norvegicus) Induced by Aloe vera Extract - Pauzan, Pauzan (Jurnal Biologi Tropis, 2025)
Incised wounds are common injuries that trigger an inflammatory response, in which Tumor Necrosis Factor-alpha (TNF-α) plays a crucial role in the pathogenesis. Aloe vera has long been recognized for its wound-healing potential; however, its molecular mechanisms particularly in modulating TNF-α expression remain incompletely understood. This study aims to investigate the effect of Aloe vera extract on TNF-α expression in incised wounds of white rats. This experimental study employed a controlled group design, involving a positive control group (K+), a negative control group (K−), and a treatment group (P), each consisting of five white rats. Incised wounds were created on the dorsum of the rats, and the treatment group received topical Aloe vera extract. TNF-α expression was evaluated using immunohistochemical methods on days 3, 7, and 14 post-wounding. The treatment group that received Aloe vera extract showed a significant decrease in TNF-α expression compared to the negative control group on days 7 and 14. Aloe vera extract modulates TNF-α expression in incised wounds of white rats, indicating its potential as a therapeutic agent in wound healing through anti-inflammatory mechanisms.